2017
DOI: 10.1097/mot.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyperlipidemia on alloimmunity

Abstract: Purpose of Review Hyperlipidemia is a co-morbidity affecting a significant number of transplant patients despite treatment with cholesterol lowering drugs. Recently it has been shown that hyperlipidemia can significantly alter T cell responses to cardiac allografts in mice, and graft rejection is accelerated in dyslipidemic mice. Here we review recent advances in our understanding of hyperlipidemia in graft rejection. Recent Findings Hyperlipidemic mice have significant increases in serum levels of pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Given the systemic effects of hyperlipidemia that promote inflammation, we examined how hyperlipidemia affects transplant outcome. We have shown that hyperlipidemia promotes accelerated rejection of vascularized cardiac allografts 16–18 . Hyperlipidemia‐induced accelerated rejection is associated with an increase in anti‐donor Th1 and Th17 responses as well as changes in Tregs and increases in serum concentrations of inflammatory cytokines 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the systemic effects of hyperlipidemia that promote inflammation, we examined how hyperlipidemia affects transplant outcome. We have shown that hyperlipidemia promotes accelerated rejection of vascularized cardiac allografts 16–18 . Hyperlipidemia‐induced accelerated rejection is associated with an increase in anti‐donor Th1 and Th17 responses as well as changes in Tregs and increases in serum concentrations of inflammatory cytokines 16 …”
Section: Introductionmentioning
confidence: 99%
“…We have shown that hyperlipidemia promotes accelerated rejection of vascularized cardiac allografts. [16][17][18] Hyperlipidemia-induced accelerated rejection is associated with an increase in anti-donor Th1 and Th17 responses as well as changes in Tregs and increases in serum concentrations of inflammatory cytokines. 16 Systemic changes induced by hyperlipidemia include increased serum levels of IL-6.…”
mentioning
confidence: 99%